Optimality conditions for a class of E-differentiable vector optimization problems with interval-valued objective functions under E-invexity - Abdulaleem, Najeeb (International journal of computer mathematics, 2023)
In this paper, a class of E-differentiable multiobjective programming with multiple objective functions and with both inequality and equality constraints is considered. The so-called E-Karush-Kuhn-Tucker necessary optimality conditions for a (weak LS-Pareto) LS-Pareto solution are established for the considered E-differentiable vector optimization problem with the multiple interval-valued objective functions. Also several sufficient optimality conditions for both LU and LS order relations are derived for such interval-valued vector optimization problems under (generalized) E-invexity hypotheses.